2022
DOI: 10.3389/fcvm.2022.842532
|View full text |Cite
|
Sign up to set email alerts
|

Early Change in Area Strain Detected by 3D Speckle Tracking Is Associated With Subsequent Cardiotoxicity in Patients Treated With Low Doses of Anthracyclines

Abstract: ObjectiveTo evaluate the prognostic impact of the parameters of myocardial deformation using three-dimensional speckle tracking echocardiography (3DSTE) in patients with breast cancer who underwent chemotherapy with low doses of anthracyclines.BackgroundChemotherapy-related cardiotoxicity has an important prognostic impact on cancer survivors. Three-dimensional STE has revealed more consistent data than two-dimensional techniques and may represent a more accurate tool in the evaluation of myocardial function i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 42 publications
(63 reference statements)
0
7
0
3
Order By: Relevance
“…They reported that the 2DGLS presented changes only at the end of the protocol, after the 240 mg/m2 dosage with no change after a lower cumulative dosage of doxorubicin. By 3DSTE they reported changes in most myocardial deformation parameters: 3D GLS, 3D GRS, 3D GCS, and 3D GAS after the cumulative dose of 240 mg/m2 of doxorubicin and no changes in rotation, torsion, or twist in any of the evaluation stages, alternatively, following a lower cumulative dose of doxorubicin (120 mg/m2), the only variable that significantly shifted was 3D GAS, so they decided that The 3D GAS early changed to below normal values was the only parameter that was associated with the subsequent decrease in LVEF during follow-up, while the other variable indices of LV mechanics derived from 2 and 3D speckle tracking analysis, as well as the conventional echocardiographic data were not predictors of CTRCD, another point they highlighted in their study was the proof of accurate reproducibility of 3DSTE, especially in 3D GCS and 3D GAS, demonstrating their dependability and accuracy indices in the assessment of ventricular mechanics [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…They reported that the 2DGLS presented changes only at the end of the protocol, after the 240 mg/m2 dosage with no change after a lower cumulative dosage of doxorubicin. By 3DSTE they reported changes in most myocardial deformation parameters: 3D GLS, 3D GRS, 3D GCS, and 3D GAS after the cumulative dose of 240 mg/m2 of doxorubicin and no changes in rotation, torsion, or twist in any of the evaluation stages, alternatively, following a lower cumulative dose of doxorubicin (120 mg/m2), the only variable that significantly shifted was 3D GAS, so they decided that The 3D GAS early changed to below normal values was the only parameter that was associated with the subsequent decrease in LVEF during follow-up, while the other variable indices of LV mechanics derived from 2 and 3D speckle tracking analysis, as well as the conventional echocardiographic data were not predictors of CTRCD, another point they highlighted in their study was the proof of accurate reproducibility of 3DSTE, especially in 3D GCS and 3D GAS, demonstrating their dependability and accuracy indices in the assessment of ventricular mechanics [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“… 23 Piveta et al indicaram que, em pacientes com câncer de mama que receberam uma dose cumulativa mais baixa de doxorrubicina (120 mg/m 2 ), apenas o parâmetro 3D-STI de strain AGS mudou, e sua mudança foi correlacionada com diminuição da FEVE (cardiotoxicidade definitiva). 38 A AGS é um índice introduzido tardiamente, representando o percentual de strain na superfície endocárdica do VE. As vantagens diagnósticas da AGS são provavelmente alcançadas por uma avaliação mais abrangente, integrando ambos movimentos, o longitudinal e o circunferencial do miocárdio.…”
Section: Discussionunclassified
“… 23 Piveta et al indicated that, in patients with breast cancer who received a lower cumulative dose of doxorubicin (120 mg/m 2 ), only the 3D-STI strain parameter GAS changed, and its change was correlated with decreased LVEF (definitive cardiotoxicity). 38 GAS is an index introduced late, representing the percentage of deformation in the LV endocardial surface area. The diagnostic advantages of GAS are probably achieved by a more comprehensive evaluation by integrating both longitudinal and circumferential motion of the myocardium.…”
Section: Discussionmentioning
confidence: 99%
“…By 3DSTE they reported changes in most myocardial deformation parameters: 3D GLS, 3D GRS, 3D GCS, and 3D GAS after the cumulative dose of 240 mg/m2 of doxorubicin and no changes in rotation, torsion, or twist in any of the evaluation stages, alternatively, following a lower cumulative dose of doxorubicin (120 mg/m2), the only variable that signi cantly shifted was 3D GAS, so they decided that The 3D GAS early changed to below normal values was the only parameter that was associated with the subsequent decrease in LVEF during follow-up, while the other variable indices of LV mechanics derived from 2D and 3D speckle tracking analysis, as well as the conventional echocardiographic data were not predictors of CTRCD, another point they highlighted in their study was the proof of accurate reproducibility of 3DSTE, especially in 3D GCS and 3D GAS, demonstrating their dependability and accuracy indices in the assessment of ventricular mechanics. [34] 3D speckle tracking echocardiography in non-breast cancer patients Not only breast cancer and its chemotherapy are the focus for this systematic review but also, we are looking at complementary data for other patients with heterogeneous malignancies and who received different chemotherapies.…”
Section: D Speckle Tracking Echocardiography In Breast Cancer Patientsmentioning
confidence: 99%